2022
DOI: 10.3390/microorganisms10061144
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Citrus Dwarfing Viroid Induced Dwarfing Phenotype of Sweet Orange on Trifoliate Orange Rootstock

Abstract: Dwarfed citrus trees for high-density plantings or mechanized production systems will be key for future sustainable citrus production. Citrus trees consist of two different species of scion and rootstock. Therefore, any observed phenotype results from gene expression in both species. Dwarfed sweet orange trees on trifoliate rootstock have been produced using citrus dwarfing viroid (CDVd). We performed RNA-seq transcriptome analysis of CDVd-infected stems and roots and compared them to non-infected controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Vd-siRNA may act as an inducer of symptom expression by mediating host mRNA cleavage or the methylation of promoter regions. Several research teams have reported the changes in host miRNA after viroid infection [ 58 , 59 , 60 , 61 ]. Numerous potential target genes for transcription factors and other regulatory proteins may occupy important positions in viroid–host interactions.…”
Section: Response Of Citrus Hosts To Viroid Infectionmentioning
confidence: 99%
“…Vd-siRNA may act as an inducer of symptom expression by mediating host mRNA cleavage or the methylation of promoter regions. Several research teams have reported the changes in host miRNA after viroid infection [ 58 , 59 , 60 , 61 ]. Numerous potential target genes for transcription factors and other regulatory proteins may occupy important positions in viroid–host interactions.…”
Section: Response Of Citrus Hosts To Viroid Infectionmentioning
confidence: 99%
“…Citrus growers worldwide are attracted to dwarfing citrus rootstocks because they are ideal for high-density plantations and are suitable for mechanized farming [ 25 ]. Dwarfing citrus rootstocks are well represented in research reports ( Table 1 ).…”
Section: Dwarfing Citrus Rootstocksmentioning
confidence: 99%
“…Plant dwarfism has been linked with several viruses and viroids [ 25 , 48 , 49 ]. The citrus exocortis viroid seems to cause dwarfism in citrus plants by increasing the aboveground hydraulic resistance [ 50 ].…”
Section: Dwarfing Citrus Rootstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) ). In recent years, next-generation sequencing (NGS) technology has enabled the global transcriptomic analyses of several different hosts infected with PSTVd ( Chi et al., 2022 ; Góra-Sochacka et al., 2019 ; Hadjieva et al., 2021 ; Więsyk et al., 2020 ), HSVd ( Xia et al., 2017 ; Xu et al., 2020 ), citrus exocortis viroid (CEVd) ( Wang et al., 2019 ), CDVd ( Lavagi-Craddock et al., 2022 ) and dendrobium viroid (DVd) ( Li et al., 2022 ). These studies have shown that several host pathways were commonly altered by pospiviroid infection, including host defence signalling, phytohormone networks, secondary metabolism, transport, transcription, as well as protein synthesis and modification ( Joubert et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%